Are cervical collars effective and safe in prehospital spinal cord injury management?. (2nd February 2020) - Hodgett, Rachel; Ward, Richard
Abstract : Background: In the UK, around 500–600 people a year sustain traumatic injuries to the spinal cord, half of which involve the cervical spine. UK ambulance guidelines stipulate that if immobilisation is indicated, the entire spine should be immobilised using an orthopaedic scoop stretcher, head restraints and a rigid cervical collar. However, the use of cervical collars is being debated in the paramedic profession. Although they were originally considered harmless and used as a precautionary measure, an increasing amount of evidence suggests otherwise and it is argued that they can do more harm than good. Therefore, it is debatable whether using them is consistent with the principles of patient safety and evidence-based practice. Aim: A literature review was carried out to comprehensively examine research surrounding the adverse effects of cervical collars and the range of movement they allow to gain a comprehensive understanding of their efficacy. Methods: The EBSCOhost Health Science Research database was searched. Seven articles were found and chosen for inclusion in the literature review. Results: Two themes were identified regarding cervical collars: adverse effects and range of movement. Conclusion: Evidence suggests that cervical collars can cause more harm than good, and UK ambulance guidelines for spinal immobilisation should be reconsidered.